Estimation of Geometric Factors for the Particle Detecting Instruments of the Geostationary Satellite GK2A at 128.2°E Longitude Based on Observations of the Outer Radiation Belt During Geomagnetically Quiet Periods - W.‐H. Seol; C.‐H. Lee; J. Seon; Y.‐C. Shin; K.‐H. Kim; D. E. Larson; G. K. Parks; J. Sample (Space Weather)
Abstract We present a method to determine energy‐dependent geometric factors for charged particle instruments in electron energy range of 125–2,200 keV aboard the geostationary satellite GEO‐KOMPSAT‐2A (GK2A), stationed at 128.2°E longitude. As deduced from the GEANT4 Monte Carlo simulation, the response function of the instrument in a matrix form was employed to undertake forward‐fitting of the differential energy spectra against various functions such as the double Maxwellian (DM), relativistic kappa (KP), and power‐law (PL). Thereby, we determined the energy‐dependent geometric factors for each energy channel and instrument. The forward‐fitting method was performed for a selected period of geomagnetically quiet days from May to November 2019, by applying stringent conditions to geomagnetic indices and the residual from the fit. It was found that the KP and DM functions provided better fits overall, whereas the PL function yielded considerably worse fits to the measurements. For the KP and DM functions, the validity of the geometric factors was examined against the distributions of the measured count rates and inferred model fluxes. The estimated model parameters, such as the spectral index from the KP function or the temperature from the DM functions, were also analyzed. The present study shows that the instruments provided quantitative observations of the outer radiation belt at a vantage point of 128.2°E longitude and allowed for a simple and reliable means to obtain electron fluxes based on combinations of results from numerical simulation, ground calibration, and space measurements.